THE EU ACCESSION AND THE IMPACT ON ROMANIA’S FOREIGN TRADE AND COMPARATIVE ADVANTAGE - Adrian Negrea (Studies and Scientific Researches: Economics Edition, 2013)
Romania’s accession to the EU was a difficult task, but doable. However, the results of this accession are only now taking shape in the form of export orientation and competitiveness. This paper thoroughly analyses the aspects regarding Romania’s foreign trade, based on the classification used by Lall (2000), with the data provided by the National Institute of Statistics on the Combined Nomenclature XXII sections, covering the 1991 – 2012 period. Furthermore, the paper addresses the concept of comparative advantage based on the Lafay indicator of Romania’s foreign trade during 1991 - 2012. The indicator is calculated based on the statistical data offered by the National Institute of Statistics of the combined nomenclature with its XXII sections combined with Lall (2000) classification. The conclusions based on prior results try to assess whether the accession to the EU has had a beneficial or harmful effect on Romania’s international trade and its comparative advantages.